Heavy Metal Accumulation in Rice (Oryza Sativa L.) from Irrigation Water Sources of Citarum River and Tarum Barat Canal to Public Health Risk - Mustofa, Ulfah Hana; Roosmini, Dwina (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2024)
Food safety are needed in Karawang District, which is the second largest rice producing area in West Java, the Citarum River water used as an irrigation source is polluted by industrial waste. This study aims to identify the heavy metal content of paddy water, soil and accumulation of rice using polluted irrigation water sources that pose a risk to public health. Total of 60 samples from water,soil,rice were measured using Atomic Absorption Spectrophotometry (AAS) and analysed for bioaccumulation factors (BAF). The questionnaire results were used to calculate farmers' health risks using deterministic and probabilistic Monte Carlo. The concentrations of water and soil in the irrigated rice fields of the Citarum River (SCT) and the irrigated rice fields of the West Tarum Canal (STBT) were still below the permitted standards. The concentrations of Pb and Cr metals in rice in SCT rice fields were above the quality standards. BAF>1 indicates Cu metal in rice in SCT and STBT rice fields can accumulate heavy metals. The results show that Hazard Index or HI>1 indicates farmers in both rice fields have a noncarcinogenic risk with a contribution level of Hazard Quotient Cu of 57.71%-63.78%. Cancer risk of Cr metal showed that exceeds the acceptable value both deterministic and probabilistic approaches, thus indicating a carcinogenic risk to farmers in both study areas. Proper monitoring of soil and irrigation is needed with prevention of consumption of contaminated rice.